Systematic analysis of composition and molecular mechanisms of action of the Vitex agnus-castus standardized extracts. Literature review - И. Ю. Торшин; О. А. Громова; О. А. Лиманова (Publishing House TRILIST, 2020)
Extracts of Vitex agnus-castus are used to regulate the menstrual cycle, in the treatment of premenstrual tension syndrome, hyperprolactinemia, and infertility. Vitex extracts component analysis showed the presence of such compounds as vitexin, rotundifuran, kastitsin, artemetin and some phytoestrogens. Extracts components are characterized with antiinflammatory, antiproliferative, antioxidant, antimicrobial (particularly antifungal), vasoprotective and analgesic effects. The role of the extracts components in modulation of opioid and dopamine receptors has been described. The paper also reviews estrogen modulating and anti-hyperprolactinemic properties of Vitex extracts